Association between grit and depressive symptoms among medical students, moderated by academic performance - Mitsuyuki Numasawa; Nobutoshi Nawa; Kumiko Yamaguchi; Keiichi Akita; Masanaga Yamawaki (Medical Education Online)
Depression amongst medical students is a crucial matter. Grit, which is a potentially modifiable psychological factor, has been inversely linked to depressive symptoms. However, it remains unclear how grit is associated with depression. This study aims to examine the relationship between grit and depressive symptoms and to further investigate the potential effect modification by academic performance on the association between grit and depression among medical students. We focus on the total grit score and its subscales, namely perseverance of effort and consistency of interest. A cross-sectional study was conducted using data from second-year medical students at Tokyo Medical and Dental University in Japan from 2020 to 2023. The participants responded to questionnaire surveys comprising the Center for Epidemiologic Studies Depression Scale and the Short Grit Scale. Linear regression analysis was performed to assess the association between grit and depressive symptoms. We also tested for effect modification by first-year Grade Point Average (GPA) on the association between grit and depression. The total grit score and its subscales, perseverance of effort and consistency of interest, were all inversely associated with depressive symptoms (b =  −4.7 [95%CI − 6.7 to − 2.6], b =  −3.7 [95%CI − 5.3 to − 2.1], b =  −1.8 [95%CI − 3.5 to − 0.2], respectively). While the interaction term for the total grit score and GPA was not significant, the interaction term for perseverance of effort and GPA was significant, indicating that the association between perseverance of effort and depression was stronger among the higher-achieving students. The interaction term for consistency of interest and GPA was also significant, indicating that the association was stronger among the lower-achieving students. We reveal a novel aspect of the association between grit and depressive symptoms in light of academic performance. The findings will contribute to future research on depression amongst medical students.